PENGARUH AUDIT TENURE DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT REPORT LAG - Evita Okta Ristina, 14.05.52.0220; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2018)
The aims of research to provide empirical evidence of the influence of audit tenure and KAP measures on audit report lag.This independent variable research consisted of audit tenure and KAP size. Dependent variable audit report lag. In this research used of sample of manufacturing company listed in the Indonesia Stock Exchange on period 2013-2016. In the sample of research is 252 company. This method uses purposive sampling. This study uses Multiple Linear Analysis technique.The result of this research shows that audit tenure has no significant negative effect on audit report lag and KAP size has negative effect to audit report lag.Keywords: audit report lag, audit tenure, KAP size